The Role Of The Honesty Canteen In Shaping The Business Ethics Of Management Students At Nusantara Pgri University, Kediri - Susi Damayanti; Tjetjep Yusuf Afandi; Zainal Arifin (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the effect of honesty cages on the development of business ethics among Management students. A quantitative approach was used, employing a simple linear regression method. The sample consisted of 39 students from Class 2G who had direct experience of using honesty canteens. Data were collected through questionnaires and analyzed using statistical software. The results of the analysis show that the honesty canteen variable significantly affects student business ethics. This is evidenced by a t-test significance value of 0.000 and a t-count value of 8.693. The F-test also produced significant results, with an F-count value of 75.570 and a significance value of 0.000. With a coefficient of determination (R²) of 0.671, 67.1% of the variation in student business ethics can be explained by the honesty canteen variable. It can therefore be concluded that honesty canteens play a role in fostering honesty, responsibility and ethics among students. These facilities are not only places for transactions, but also serve as a means of character education relevant to business ethics. This study therefore recommends developing and integrating honesty canteens into character education programs in higher education institutions